1978
DOI: 10.1136/jcp.31.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Microcult system for isolating and identifying Neisseria gonorrhoeae.

Abstract: SUMMARY Specimens from 95 patients attending a venereal diseases clinic were examined for gonococci by three methods-a conventional culture technique using modified Thayer-Martin medium, microscopy of a Gram-stained direct smear, and the Microcult system. For 56?' of the specimens the results by all three methods agreed. Assuming the results obtained by culture on Thayer-Martin medium to be correct, the largest source of error was due to false-positive results: microscopy gave 26 and Microcult gave 15 such res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…We agree with Willcox and John (1976) and Williams et al (1978) that Microcult-GC may be useful in areas or countries which lack laboratory facilities. In addition, the test allows subculture of gonocococci without the need to incorporate antibiotics into the medium used, which might be an advantage in some laboratories.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We agree with Willcox and John (1976) and Williams et al (1978) that Microcult-GC may be useful in areas or countries which lack laboratory facilities. In addition, the test allows subculture of gonocococci without the need to incorporate antibiotics into the medium used, which might be an advantage in some laboratories.…”
Section: Discussionsupporting
confidence: 81%
“…Unlike Williams et al (1978) we found that subculture from Microcult-GC was easy and the results correlated completely with those of VCNT culture. Our method of subculture delivered a heavier inoculum and we minimised delay after oxidase-testing.…”
Section: Discussionmentioning
confidence: 56%